Evaluation of Demographic Characteristics, Working Conditions, Depression, Anxiety and Insomnia Levels of Health Workers During the COVID-19 Pandemic Period - Suat Sincan; Gülden Sincan; Esra Çınar Tanrıverdi; Mustafa Bayraktar; Mine Şahingöz; Zülal Özkurt; Yasemin Çayır (Bagcilar Medical Bulletin, 2025)
Objective: The coronavirus disease-2019 (COVID-19) pandemic has caused an increase in psychiatric disorders such as depression, anxiety, insomnia, and suicidality in the community. Therefore, we aimed to determine the frequency, severity, and factors affecting depression, anxiety, and sleep disorders in healthcare workers during the pandemic. Method: In our study, 558 healthcare workers were surveyed online, and their occupation, their status as frontline workers, their chronic diseases, their COVID-19-related training, the presence of their personal protective equipment, the frequency and duration of their shifts in pandemic units, and their exposure to negative and positive discrimination were determined. The generalized anxiety disorder 7, insomnia severity index, and center for epidemiologic studies depression scale questionnaires were administered to all patients. Results: It was determined that 28% of the participants had insignificant clinical insomnia, 43.5% had subthreshold insomnia, 22.4% had moderate clinical insomnia, and 6.1% had severe clinical insomnia. Of the subjects, 34.9% had mild anxiety, 21.3% had moderate anxiety, and 12.5% had severe anxiety. Of the participants, 11.8% were mildly depressed, 26% were moderately depressed, and 31.4% were severely depressed. Insomnia, anxiety, and depression were more severe in women, frontline workers, those who worked shifts in COVID-19 clinics, nurses, those without personal protective equipment, those subjected to negative discrimination, and those implied by family or friends to be carriers of the virus. Conclusion: Depression and anxiety are more frequent and severe among frontline healthcare workers during pandemic periods. Therefore, necessary social and psychological support should be provided to these individuals.